CAPABILITY INDICES FOR CONTROL CHARTS BASED ON REGRESSION MODELS - Souza, Fernanda Siqueira; Pedrini, Danilo Cuzzuol; ten Caten, Carla Schwengber (Brazilian Journal of Operations & Production Management, 2015)
Process capability analysis is extremely important for optimization and quality improvement. It verifies whether the process under analysis is capable of producing items within engineering and customers’ specifications. The use of capability indices when assumptions are not satisfied leads to erroneous conclusions, compromising the study and analysis of the process, jeopardizing the fulfillment of requirements from management or external customers. Aiming at filling a gap identified in the literature, the main contributions of this work are: (i) proposition of capability indices for processes monitored through control charts based on regression models, for symmetric and asymmetric specifications; and (ii) comparison of the proposed indices with traditional capability indices through a simulated process.